THE GUIDANCE OF TECHNOPRENEURSHIP USING EXPERT SYSTEM COMPUTING APPROACH BASED ON ENTREPRENEURIAL VALUES AND MULTIPLE INTELLIGENCES - Indra Hastuti; Singgih Purnomo; Wiji Lestari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
This study aims to build the Guidance of technopreneurship, especially Information Technology (IT) technopreneurship using expert system approach based on entrepreneurial values and multiple intelligences.The research consists of several steps : system analysis and design, system development and test and implementation system.The result is the guidance of technopreneurship using an expert system. Expert system consists of expertise domain, knowledge representation, rules, and input and output data. Data input consists of indicators of entrepreneurial values and multiple intelligences. The data output consists of conformity with 8 IT tecnopreneurships ie Software Application Developer, Data Analyst, System Analyst, Software Engineering, Computer Network Engineer, Graphics Designer & Animator, Multimedia System Developer and Embedded & Computer System Engineer.he test results with internal testing and external testing show the system works well. Keyword : Guidance;Technopreneurships; Information Technology Expert System; Entrepreneurial Values; Multiple Intelligences